SHAPING BUSINESS ETHICS IN THE DIGITAL ERA OF BANKING COMPANIES: DOES GOOD CORPORATE GOVERNANCE MATTER? - Citrawati Jatiningrum; Aza Azlina Md Kassim; Indah Lia Puspita; Hardini Ariningrum (JMBI (Journal of Marketing and Business Intelligence), 2026)
The digital era has transformed banking operations through advanced technologies, data analytics, and decision making, raising new challenges and opportunities for business ethics. This study examines the relationship between Good Corporate Governance (GCG) and business ethics in banking companies in the context of digitalization. Using a quantitative research design, the study analyzes whether strong corporate governance implementation, good corporate governance policy, IT Governance shape ethical behavior and corporate integrity in digital banking environments. The findings suggest that good corporate governance matters significantly: banks with robust governance frameworks are more likely to embed ethical principles into digital practices, enhance transparency, and strengthen stakeholder trust. The result study show that GCG implementation, GCG Policy and IT Governance significantly as a control mechanism to ensure that the company continues to operate within ethical corridors. The study contributes to the literature by integrating business ethics, corporate governance, and digital era banking, and it offers practical implications for banks, regulators, and policymakers seeking to align technological innovation with ethical and governance standards.